Cystic proliferation of germline stem cells is necessary to reproductive success and normal mating behavior in Medaka - Padilla, Luisa F Arias; Castañeda-Cortés, Diana C. [UNESP]; Rosa, Ivana F. [UNESP]; Acosta, Omar D Moreno; Hattori, Ricardo S. [UNESP]; Nóbrega, Rafael H.; Fernandino, Juan I. (eLife, 2021)
The production of an adequate number of gametes is necessary for normal reproduction, for which the regulation of proliferation from early gonadal development to adulthood is key in both sexes. Cystic proliferation of germline stem cells is an especially important step prior to the beginning of meiosis; however, the molecular regulators of this proliferation remain elusive in vertebrates. Here, we report that ndrg1b is an important regulator of cystic proliferation in medaka. We generated mutants of ndrg1b that led to a disruption of cystic proliferation of germ cells. This loss of cystic proliferation was observed from embryogenic to adult stages, impacting the success of gamete production and reproductive parameters such as spawning and fertilization. Interestingly, the depletion of cystic proliferation also impacted male sexual behavior, with a decrease of mating vigor. These data illustrate why it is also necessary to consider gamete production capacity in order to analyze reproductive behavior.